Involvement of AlpV, a New Member of the Streptomyces Antibiotic Regulatory Protein Family, in Regulation of the Duplicated Type II Polyketide Synthase alp Gene Cluster in Streptomyces ambofaciens - Aigle, Bertrand (American Society for Microbiology, 2005)
A type II polyketide synthase gene cluster located in the terminal inverted repeats of Streptomyces ambofaciens ATCC 23877 was shown to be responsible for the production of an orange pigment and alpomycin, a new antibiotic probably belonging to the angucycline/angucyclinone class. Remarkably, this alp cluster contains five potential regulatory genes, three of which (alpT, alpU, and alpV) encode proteins with high similarity to members of the Streptomyces antibiotic regulatory protein (SARP) family. Deletion of the two copies of alpV (one in each alp cluster located at the two termini) abolished pigment and antibiotic production, suggesting that AlpV acts as a transcriptional activator of the biosynthetic genes. Consistent with this idea, the transcription of alpA, which encodes a ketosynthase essential for orange pigment and antibiotic production, was impaired in the alpV mutant, while the expression of alpT, alpU, and alpZ, another regulatory gene encoding a γ-butyrolactone receptor, was not significantly affected. Real-time PCR experiments showed that transcription of alpV in the wild-type strain increases dramatically after entering the transition phase. This induction precedes that of alpA, suggesting that AlpV needs to reach a threshold level to activate the expression of the structural genes. When introduced into an S. coelicolor mutant with deletions of actII-ORF4 and redD, the SARP-encoding genes regulating the biosynthesis of actinorhodin and undecylprodigiosin, respectively, alpV was able to restore actinorhodin production only. However, actII-ORF4 did not complement the alpV mutant, suggesting that AlpV and ActII-ORF4 may act in a different way.